Entomobryoidea (Collembola) from Himachal Pradesh (India) in the Himalayas - Baquero, Enrique; Mandal, Gurupada; Jordana, Rafael (Zootaxa, 2015)
Collections made during March–April, 2010, October–November, 2010 and 2011 from different districts of Himachal Pradesh, India, by the Apterygota section of the Zoological Survey of India contained new species of Entomobryoidea. Localities sampled were Solan, Shimla, Kullu, Bilaspur, Kagra, Chamba and Sirmaur districts of Himachal Pradesh. Collections were mainly made using an aspirator from leaf litter, mosses, under stones, flowering garden plants and river embankments, wetlands and rotting logs. Sixteen species were found, belonging to genera: Entomobrya, Himalanura, Homidia, Sinella, Willowsia, Lepidocyrtus (Acrocyrtus), Lepidocyrtus (Cinctocyrtus), Seira, Drepanosira and Salina. Twelve of these have been described as new species.